100 years of landscape architecture education in Europe: lessons from the early pioneers for our visions of the future - Birli, Barbara; Fetzer, Ellen (4D Journal of Landscape Architecture and Garden Art, 2019)
Our presentation has two goals: First, to look back into the founding period of landscape architecture education in Europe in order to understand the major driving forces behind the evolution of these programmes. We will talk about the background of the first teachers and the early concepts for landscape architecture pedagogy. On that basis, we outline the tuning process of landscape architecture education that started post-1989, the turning point that boosted the establishment of the European Higher Education Area. We will finish with a vision of how landscape architecture education may develop in the future in response to global sustainability challenges, digitalisation and the increasing internationalisation and individualisation of education.